A composite cutting process for semiconductor materials containing a back gold layer

Through grinding wheel cutting, the cutting groove is formed and laser internal modified cutting is combined with the problem of alloy back gold layer adhesion and thermal damage in semiconductor material cutting, achieving high-efficiency and low-damage cutting effect, ensuring cutting quality and efficiency.

CN115770960BActive Publication Date: 2025-01-07HUNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211465176.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-25
Filing Date
2022-11-22
Publication Date
2025-01-07
Estimated Expiration
2042-11-22

AI Technical Summary

Technical Problem

In the prior art, when cutting semiconductor materials, especially materials containing back gold layer, it is difficult to achieve high-efficiency and low-damage cutting, and laser-modified cutting, there are problems of alloy back gold layer adhesion and thermal damage, affecting the cutting quality and efficiency.

Method used

The back gold layer is cut into the cutting groove, and combined with the laser internal modification and cutting process, the removal of the alloy back gold layer and the uniform propagation of laser energy are ensured by controlling the cutting depth of the grinding wheel and the laser scanning parameters, and the removal of the alloy back gold layer and the uniform propagation of laser energy are reduced, thereby reducing thermal damage.

Benefits of technology

High-efficiency and low-damage cutting is achieved, ensuring cutting quality and efficiency, avoiding layering and thermal damage of the dorsal gold layer, and obtaining good cutting surface and edge quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115770960B_ABST
    Figure CN115770960B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite cutting process for semiconductor materials containing a back gold layer, which comprises the following steps: 1) cutting the back gold layer of the semiconductor material with a grinding wheel to form a cutting groove; 2) laser internal modification cutting process is used to perform laser internal cutting on the semiconductor material; the incident surface of the laser is away from the back gold layer, and the cutting path of the laser corresponds to the cutting groove; 3) the semiconductor material is subjected to a splitting process to separate the semiconductor material into several pieces. The composite cutting process of the present invention obtains a good cutting surface, with a straightness of ≤10μm, a broken edge / broken angle of ≤10μm, and no obvious stratification between the back gold layer and 4H‑SiC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite cutting process for a semiconductor material containing a back gold layer, belonging to the technical field of semiconductor material cutting. Background Art

[0002] Semiconductor cutting is one of the key technologies in the semiconductor manufacturing process. At present, a cutter wheel is usually used to cut semiconductor materials. However, due to the high hardness and strong brittleness of the third-generation semiconductor materials, the efficiency of cutting with traditional cutter wheels is extremely low, and the cutter wheels are severely worn, making it difficult to meet processing requirements. Compared with traditional cutter wheel cutting, laser cutting has rapidly occupied the traditional mechanical cutting market due to its advantages such as environmental protection, high efficiency, and small edge collapse. The mainstream cutting technologies of laser cutting are divided into two types: ablation cutting and modified cutting. Compared with ablation cutting, modified cutting is more suitable for cutting semiconductor materials because it has no metamorphic layer. However, for semiconductor materials after the back-gold process, only laser modification cutting is used. The alloy back-gold layer will block the penetration and convergence of the laser, resulting in the phenomenon of alloy back-gold layer adhesion, which seriously restricts the cutting quality and cutting efficiency of semiconductor cutting. At present, there are two solutions to the problem of alloy back gold adhesion: 1. Processing cutting paths on the alloy back gold layer by chemical etching. This method has problems such as complex procedures and long time consumption; 2. Processing cutting paths on the alloy back gold layer by laser ablation. This method is difficult to control the thermal damage of laser ablation, which can easily cause a splash zone to form at the edge of the cut, and can easily cause problems such as peeling between the back gold layer and the SiC substrate, affecting subsequent packaging. Summary of the invention

[0003] In order to cut semiconductor materials containing a back gold layer with high efficiency and low damage and obtain good cutting quality, the present invention provides a composite cutting process for semiconductor materials containing a back gold layer, and the specific technical scheme is as follows.

[0004] A composite cutting process for semiconductor materials containing a back gold layer, characterized by comprising the following steps:

[0005] 1) Using a grinding wheel to cut the back gold layer of the semiconductor material to form a cutting groove;

[0006] 2) Using a laser internal modification cutting process to perform laser internal cutting on the semiconductor material; the incident surface of the laser is away from the back gold layer, and the cutting path of the laser corresponds to the cutting groove;

[0007] 3) Performing a splitting process on the semiconductor material to separate the semiconductor material into several pieces.

[0008] Further, the depth of the cutting groove is 4-30 μm, the cutting linear speed of the grinding wheel is 20-50 m / s, and the cutting speed of the grinding wheel is 10-300 mm / s. Preferably, the depth of the cutting groove is 10-30 μm, the cutting linear speed of the grinding wheel is 30 m / s, and the cutting speed of the grinding wheel is 10 mm / s.

[0009] When a grinding wheel is used to cut the back gold layer of a semiconductor material to form a cutting groove, if the processing depth is less than the thickness of the back gold layer, the back gold layer cannot be cut through, and the alloy back gold layer will be delaminated. Therefore, in order to ensure that the alloy back gold layer is completely removed, first of all, the processing depth must be greater than the alloy back gold layer. Since the processing object is a laminated composite material composed of a plastic alloy back gold layer and a brittle silicon carbide, when processing the laminated composite material, if the selected processing depth is too large, it will cause defects such as large-sized brittle pits and sub-surface cracks in the brittle silicon carbide layer, and the alloy back gold layer will peel off, and subsequent composite laser internal modification will not be possible, and even the chip will break. Therefore, in order to avoid the peeling of the alloy back gold layer and the sub-surface cracks do not affect the subsequent laser internal modification and cutting, secondly, the processing depth must be accurately controlled within a certain range. In order to accurately control the processing depth, the present invention derives the critical depth of brittle-plastic transition of the laminated composite material by grinding for the laminated composite material composed of an alloy back near layer and silicon carbide, and the process is as follows:

[0010] Step 1: Calculate the maximum undeformed chip thickness of a single abrasive grain on the alloy backing gold layer and silicon carbide layer (reference Figure 1 );

[0011] Maximum undeformed chip thickness of a single abrasive grain in the back metal layer h m1 :

[0012]

[0013] Maximum undeformed chip thickness of a single abrasive grain in the silicon carbide layer h m2 :

[0014]

[0015] Where: N d is the number of effective cutting edges per unit area of ​​the grinding wheel; r is the aspect ratio of the undeformed chip section, usually r = 4tanθ, θ is the half angle of the abrasive cone top; v w is the feed speed of the workpiece; v s is the grinding wheel speed; d s Grinding wheel diameter; a p is the total grinding depth; a p1 is the thickness of the alloy back gold layer.

[0016] Step 2: Calculate the grinding depth a of the ductile domain of the brittle material and silicon carbide layer DRG ;

[0017]

[0018] In the formula, K Id is the dynamic fracture toughness of the material, E is the elastic modulus of the material, H is the microhardness of the material, and θ is the top half angle of the diamond indenter.

[0019] Step 3: Set the maximum undeformed chip thickness of a single abrasive grain in the silicon carbide layer to h m2 Less than the grinding depth a of the ductile region of the silicon carbide layer DRG , substituting the grinding parameters, we can obtain the grinding parameters that can achieve the ductile domain of silicon carbide layer:

[0020] h m2 ≤a DRG

[0021] In the present invention, when the grinding parameters are controlled within the conditions that the average size of the abrasive grains on the grinding wheel surface is 3-15 μm, the cutting line speed of the grinding wheel is 20-50 m / s, and the cutting speed of the grinding wheel is 10-300 mm / s, the cutting depth of the quasi-ductile domain grinding of the material can be 4-30 μm. Finally, the processing depth is determined to be 4-30 μm, within which the alloy back gold layer can be guaranteed to have no delamination or peeling, and the subsequent laser modification and cutting process can be not affected.

[0022] Furthermore, the process parameters adopted by the laser internal modification cutting process are: single pulse energy of 1-5W, pulse width of 10-200ps, scanning speed of 300-1000mm / s and scanning times of 2-20 times.

[0023] After the laser is incident on the surface of the material, part of the laser energy is reflected on the surface, and the other part enters the interior of the material. In addition, part of the laser energy that enters the interior of the material is absorbed by the material. Therefore, there is energy loss in the propagation process of the laser energy before it is focused inside the material. Moreover, during the laser internal modification and cutting process, the laser will be focused inside the SiC material through the interface between the air and SiC with different refractive indices. Since the refractive index of the air and SiC materials does not match, spherical aberration will inevitably occur. The principle of spherical aberration is as follows: Figure 2 As shown. After being refracted by the spherical surface, the concentric light beams are no longer concentric light beams, but converge at different positions on the optical axis. The intersection of the light rays has different degrees of deviation from the ideal intersection point. Spherical aberration is used to describe the degree of deviation of the intersection point of the light rays from the ideal intersection point. The existence of spherical aberration will cause the focused spot size to become larger, thereby reducing the laser power density, failing to reach the threshold laser energy required for material modification, hindering the laser modification process, and making it impossible to complete the laser internal modification cutting.

[0024] When laser internal modification cutting, the control of laser power is the key to obtain better laser processing quality. When the laser power is high, such as Figure 3 As shown in (a) and (b), there is a lot of thermal damage on the surface and inside of the laser modified cutting, and the cutting quality is poor. Figure 3 As shown in (c) and (d), the surface quality of the laser-modified cutting is improved, but there is a local unmodified area near the inner part of the back gold layer, which will affect the coupling of laser thermal cracks and mechanical cracks caused by micro-grinding.

[0025] In order to control the laser heat input, the energy loss during laser propagation and the influence of spherical aberration effect on laser modification are mathematically described and quantitatively calculated theoretically to study the cutting process scheme for regulating thermal damage. In order to simplify the calculation of the laser energy loss during laser propagation, the laser energy loss is described by the change of laser power during laser transmission. Assuming that the initial power of the laser is P0, after the laser is vertically irradiated to the surface of the transparent material, the laser will be reflected, and the part of the laser power lost by reflection is P r , the reflectivity R of the material to the laser energy f It can be expressed as P r / P0. The laser power incident on the transparent material is (1-R f )P0.

[0026] When the laser beam is transmitted inside the material, the laser power will decrease as the laser transmission distance increases due to the absorption of laser energy by the material. For a laser beam transmitted in a direction perpendicular to the surface of an object, when the internal focusing depth of the laser beam is z, assuming that the laser beam transmits a distance of dz and the power drops to dP, the laser power attenuation rate dP / P should be proportional to dz, that is:

[0027] dP / P=-adz (1.1)

[0028] Where α represents the absorption coefficient of the material to light. Solving the differential equation of formula (1.1), the attenuation law of the laser power inside the material is:

[0029] P=P0(1-R f )exp(-αz) (1.2)

[0030] The laser wavelength used is 1030nm. At a wavelength of 1030nm, the refractive index n of single crystal 4H-SiC is 2.58, and the reflectivity R f is 0.19, and the absorption coefficient α of single crystal 4H-SiC to laser is 2.5*10 5 m -1The thickness of the SiC wafer used in the experiment is 350μm. The laser energy attenuation increases with the increase of the focus depth. According to formula 1-2, the laser power at the maximum focus depth of 350μm is calculated as: P = 0.74P0. When the laser is focused on the back of the wafer after transmitting 350μm inside the SiC wafer, the laser power is attenuated by 74%.

[0031] Theoretical calculation of the effect of spherical aberration on laser power density. When the laser beam converged by the objective lens passes through the interface between air and SiC with different refractive indices and is focused inside the SiC material, due to the spherical aberration effect, the actual focal length is different from the geometric focal length of the objective lens itself, such as Figure 2 As shown, the actual focal position is lower than the geometric optical focal position. Assuming the focal length of the objective lens is f, the diameter of the laser beam passing through the objective lens is D, the refractive index of the material is n2, the radius of the laser beam when passing through the interface between air and transparent material is r, the distance between the objective lens and the surface of the transparent material is L, the actual focusing depth of the laser is z', the maximum angle between the laser beam and the z-axis under geometric focusing is a, and the maximum angle between the laser beam transmission and the z-axis under actual focusing is b. According to the mathematical geometric relationship:

[0032]

[0033] Solving it yields:

[0034]

[0035] The relationship between z and a is as follows:

[0036]

[0037] According to the definition of refractive index and the relationship between trigonometric functions:

[0038]

[0039] The expression of tan b can be obtained from formula (1.6), and then tan b is substituted into formula (1.5) to obtain the distance the laser beam travels from the incident surface of the material to the actual focus:

[0040]

[0041] Spherical aberration includes axial spherical aberration and vertical spherical aberration. Axial spherical aberration causes the laser focus to shift and the focus spot size to increase. In order to simplify the calculation of the effect of spherical aberration on laser power density, this section only considers axial spherical aberration. The calculation formula of axial spherical aberration is:

[0042]

[0043] Under geometric focusing, the diameter of the focused spot is d. The existence of axial spherical aberration will make the actual focused spot no longer a circle with a diameter of d, but the laser energy is distributed within the range of an ellipse with l and d as the diameter, and the area of ​​the focused spot becomes larger. Moreover, it can be seen from formula (1.8) that the axial spherical aberration increases with the increase of the focusing depth.

[0044] According to the definition of power density, if the laser power incident on the focal plane is P and the focused spot area is S, the laser power density is:

[0045]

[0046] When the focal depth z is 0, the area of ​​the focused spot is πd 2 / 4, laser power is P0, laser power density is F0; when the focusing depth is z, the area of ​​the focused spot is πld / 4, the laser power is P, and the laser power density is F. Considering the influence of the energy loss of laser transmission and the spherical aberration effect on the laser power density, we have:

[0047]

[0048] The energy loss of laser transmission and spherical aberration will both cause the laser power density to decrease as the focus depth increases, and the superposition of the two will cause the laser power density to decrease to a greater extent. The laser power density F = 0.23F0 at a focus depth z of 350μm is calculated by formula (1.10). Theoretical calculations show that the laser transmission energy loss and spherical aberration effect cause the laser power density to decay to 23%.

[0049] Based on the results of the mechanism analysis of thermal damage to the cutting sidewall, the high pressure on the surface of the modified layer formed by laser scanning will inhibit the thermal decomposition of SiC. When the modified layer is completely formed inside the wafer, the surface of the modified layer is subjected to high pressure. Therefore, by adjusting the focusing depth of the laser beam inside the wafer so that the modified layer is completely formed inside the wafer, the thermal decomposition of SiC can be suppressed and the thermal damage to the cutting sidewall can be regulated. Laser internal modified cutting uses the crack extension between modified layers to achieve wafer segmentation. However, the maximum length of crack extension inside the SiC material is 50μm, so for a 350μm thick wafer, at least 7 modified layers need to be formed inside the wafer. Taking into account the suppression of crack extension between modified layers and the thermal decomposition of SiC, low-damage laser internal modified cutting requires the formation of more than 7 modified layers, and the modified layer is completely located inside the SiC wafer to form a physical modified layer, and the surface of the modified layer is subjected to high pressure. The schematic diagram of the adjustment of the distribution of the physical modified layer formed inside the wafer is as follows: Figure 4 shown.

[0050] Based on the above theoretical calculation results on the influence of laser transmission energy loss and spherical aberration on laser power density, when laser internal modification cutting is performed, when the laser internal focus depth is large, the laser power density attenuates greatly. In order to ensure the laser modification process of SiC materials, it is necessary to increase the laser power to compensate for the decrease in laser power density caused by energy loss and spherical aberration. When the process controls thermal damage, because the focus depth of the first laser scan is the largest, a larger laser power is selected. As the number of scans increases, the focus depth of each laser scan decreases, and the laser power density will increase accordingly. As the heat accumulation increases, the power of each laser scan is reduced one by one, and the power of the last laser scan is reduced to 23% of the first scan. The variable power multi-scan process scheme of scanning one by one and decreasing laser power can not only ensure the formation of the modified layer, but also reduce the heat accumulation of each laser scan and inhibit the formation of thermal damage. While decreasing the laser power one by one, a larger scanning speed is selected for each scan to further reduce the heat accumulation of the laser scanning process and inhibit the generation of thermal damage.

[0051] In summary, the low-damage laser internal modification cutting process controls thermal damage by comprehensively adjusting the position of the modified layer, laser power and scanning speed. The preferred process scheme is that laser scanning forms more than 7 modified layers, all modified layers are located inside the wafer, each laser scan has a fixed large scanning speed, and the laser power decreases from one laser scan to another. Based on the above theoretical analysis, the laser internal modification cutting process parameters are determined as follows: laser internal scanning forms 7 modified layers, each laser scan has a fixed large scanning speed, and the laser power decreases from one laser scan to another, which are set to 5.0, 4.3, 3.8, 3.1, 2.5, 1.7, and 1.1 from top to bottom. The low-damage laser internal modification cutting process parameters are shown in Table 1.

[0052] Table 1 Low damage laser internal modification cutting process parameters

[0053]

[0054] Based on the above theory, laser internal modification cutting experiments were carried out and good cutting quality was obtained. Figure 5 , 6 shown.

[0055] The composite cutting process of the present invention is used to obtain a good cutting surface with a straightness of ≤10 μm, an edge collapse / angle collapse of ≤10 μm, and no obvious delamination between the back gold layer and the 4H-SiC. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 It is a schematic diagram of the maximum undeformed chip thickness of a single abrasive grain in the grinding of the back gold layer and silicon carbide surface;

[0057] Figure 2It is a schematic diagram of the formation principle of spherical aberration;

[0058] Figure 3 (a) is the surface thermal ablation defect when the laser power is high; Figure 3 (b) Internal thermal ablation defects when the laser power is high; when the laser power is low, Figure 3 (c) is the improvement of surface quality when the laser power is lower; Figure 3 (d) When the laser power is low, there is a local unmodified area near the epitaxial layer;

[0059] Figure 4 This is a schematic diagram of the distribution of the physical modified layers (1#-7#) of SiC wafers;

[0060] Figure 5 It is the surface quality of the kerf using the laser internal modification cutting process parameters shown in Table 1;

[0061] Figure 6 is the internal quality of the kerf using the laser internal modification cutting process parameters shown in Table 1, where (a) is an enlarged view of the lower box area in (b); (c) is an enlarged view of the upper box area in (b);

[0062] Figure 7 It is a flow chart of the composite cutting process of the semiconductor material containing the back gold layer of the present invention;

[0063] Figure 8 It is a schematic diagram of the composite cutting process of the semiconductor material containing the back gold layer of the present invention;

[0064] Fig. 9 This is the microscopic morphology of the interface between the cutting sidewall back gold layer and 4H-SiC in Example 1;

[0065] Fig.10 This is the microscopic morphology of the interface between the cutting sidewall back gold layer and 4H-SiC in Example 2;

[0066] Fig.11 This is the microscopic morphology of the slit side wall after laser internal modification cutting in Example 2;

[0067] Fig.12 This is the microscopic morphology of the cutting groove of the back gold layer in Example 2;

[0068] Fig.13 This is the microscopic morphology of the epitaxial layer of Example 2;

[0069] Fig.14 This is a nanoindentation stress-strain curve diagram of the kerf edge corresponding to different cutting depths in Example 7.

[0070] In the figure: back gold layer 1, grinding wheel 2, sub-surface damage area 3, laser beam 4, modified layer 5. DETAILED DESCRIPTION

[0071] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0072] Example 1

[0073] The semiconductor material containing the back gold layer is the third generation semiconductor material silicon carbide (SiC). The total thickness of the SiC epitaxial wafer is 370 μm, which includes an average back gold layer of about 1.7 μm thick (thickness ranges from 1 to 4 μm).

[0074] The flow chart of composite cutting of semiconductor materials with back gold layer is as follows Figure 7 The schematic diagram of compound cutting is shown in Figure 8 As shown, firstly, a grinding wheel 2 is used to cut the back gold layer of the semiconductor material to form a cutting groove. The grinding wheel model is an ultra-thin resin bond diamond grinding wheel of D1000C75RG67, the grinding wheel speed is 30m / s (linear speed), the cutting speed is 10mm / s, and the cutting depth is 40μm; then, the semiconductor material is laser internally cut by using a laser internal modification cutting process; the incident surface of the laser beam 4 is away from the back gold layer 1, and the cutting path of the laser corresponds to the cutting groove. The parameters of the laser modification cutting are: single pulse energy of 5W, pulse width of 100ps, scanning speed of 300mm / s and scanning times of 2 times. After laser internal modification cutting, a modified layer 5 is formed in the 4H-SiC region. After laser modification cutting, the semiconductor material is subjected to a cracking process.

[0075] The microstructure of the interface between the back gold layer and 4H-SiC on the cutting side wall after grinding wheel cutting is as follows: Fig. 9 As shown in the figure, there is no obvious stratification between the back gold layer and the 4H-SiC. A 4H-SiC sub-surface damage area 3 with a (thickness) size greater than 10 μm appears in the 4H-SiC area. There will be metamorphic layers such as microcracks and polycrystalline structure in the sub-surface damage area 3. If the metamorphic layer is too thick, it will affect the transmission and focusing of the laser beam in the next process inside the material, hindering the subsequent insufficient laser internal modification and cutting. After the splitting, the sub-surface damage area is prone to edge collapse / angle collapse defects.

[0076] Example 2

[0077] Compared with Example 1, Example 2 uses different grinding wheel cutting parameters and laser modified cutting parameters. The grinding wheel speed in Example 2 is 40 m / s (linear speed), the cutting speed is 100 mm / s, and the cutting depth is 30 μm; the parameters of laser modified cutting are: single pulse energy is 5 W, pulse width is 100 ps, ​​scanning speed is 1000 mm / s, and scanning times are 2 times.

[0078] The microstructure of the interface between the back gold layer and 4H-SiC on the cutting side wall after grinding wheel cutting is as follows: Fig.10As shown in the figure, there is no obvious stratification between the back gold layer and the 4H-SiC. In the 4H-SiC area, there is only subsurface damage less than 10μm in local areas, which has little effect on the subsequent laser internal modification cutting. The microstructure of the cutting side wall after laser internal modification composite cutting is shown in the figure. Fig.11 As shown in the figure, it can be seen that the cutting modification points are evenly distributed and there is no thermal damage. Fig.12 This is the micro-morphology of micro-grinding of the back gold layer. Micron-scale granular SiC chips and curly alloy chips remain on the edge of the cutting groove. At the same time, there are obvious plastic wear marks and a small number of tiny brittle pits at the bottom of the cutting groove, indicating that the back gold layer has been completely removed, which is plastic removal; SiC has been partially removed, which is powder removal. Fig.13 This is the microscopic morphology of the epitaxial layer. The cut edges are vertical, and there are no defects such as edge collapse and delamination of the epitaxial layer.

[0079] Example 3

[0080] Compared with Example 2, Example 3 uses different grinding wheel cutting parameters and laser modified cutting parameters. The grinding wheel speed in Example 3 is 50m / s (linear speed), the cutting speed is 300mm / s, and the cutting depth is 10μm; the parameters of laser modified cutting are: single pulse energy is 1W, pulse width is 200ps, scanning speed is 300mm / s, and scanning times are 20 times. The cutting quality obtained in Example 3 is equivalent to that in Example 2.

[0081] Example 4

[0082] Compared with Example 2, Example 4 uses different grinding wheel cutting parameters and laser modified cutting parameters. The grinding wheel speed in Example 4 is 20 m / s (linear speed), the cutting speed is 10 mm / s, and the cutting depth is 4 μm; the parameters of laser modified cutting are: single pulse energy is 3 W, pulse width is 10 ps, ​​scanning speed is 300 mm / s, and scanning times are 20 times.

[0083] The cutting quality obtained in Example 4 is equivalent to that in Example 2.

[0084] Example 5

[0085] Compared with Example 2, Example 5 uses different grinding wheel cutting parameters. The grinding wheel speed in Example 5 is 40 m / s (linear speed), the cutting speed is 100 mm / s, and the cutting depth is 3 μm; the parameters of laser modified cutting are: single pulse energy is 5 W, pulse width is 100 ps, ​​scanning speed is 1000 mm / s, and scanning times are 2 times.

[0086] After the splitting process, it was found that the 4H-SiC and the back gold layer of the solution of Example 5 were partially delaminated. Since the cutting groove of the grinding wheel was shallow, the local alloy back gold layer was not cut through, and after artificial tearing, the alloy back gold layer was delaminated.

[0087] Example 6

[0088] Compared with Example 2, Example 6 is different from Example 2 in that: the incident surface of the laser is the back gold layer 1, and the laser is modified and cut along the cutting groove, and it is found that the modified cutting fails. On the one hand, the cutting groove will block part of the laser and reduce the energy of the laser; on the other hand, the subsurface damage area produced by the grinding wheel cutting will hinder the penetration and focusing of the laser, resulting in the inability to form an effective laser modified layer in the 4H-SiC area.

[0089] Example 7

[0090] Compared with Example 1, the difference between Example 7 and Example 1 is that the cutting depth of the grinding wheel is set to 30 μm, 20 μm, 10 μm and 50 μm respectively, and the compression stress strain test is performed on the cut edge of the sample after the split treatment. The test results are as follows: Fig.14 As shown in the figure, there is no gap between the back gold layer and the SiC substrate at the edge of the cut with a cutting depth of 10-30μm, but there is residual tensile stress. As the cutting depth increases, the residual tensile stress value increases. Fig.14 It shows that when the cutting depth of the grinding wheel increases to 50μm, a peeling gap of about 1μm appears between the 4H-SiC and the back gold layer after the splitting process.

[0091] The embodiments of the present invention are described above in conjunction with the accompanying drawings. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention is not limited to the above-mentioned specific implementations, which are merely illustrative and not restrictive. Under the enlightenment of the present invention, those skilled in the art can also make many forms without departing from the scope of protection of the present invention and the claims, all of which belong to the protection scope of the present invention.

Claims

1. A composite cutting process for semiconductor materials containing a back gold layer, characterized in that: The following steps are involved: 1) Use a grinding wheel to cut the back gold layer of the semiconductor material to form a cutting groove; 2) Using a laser internal modification cutting process to perform laser internal cutting on the semiconductor material; the incident surface of the laser is away from the back gold layer, and the cutting path of the laser corresponds to the cutting groove; 3) Splitting the semiconductor material into pieces; The depth of the cutting groove is 4-30 μm, the cutting linear speed of the grinding wheel is 20-50 m / s, and the cutting speed of the grinding wheel is 10-300 mm / s; The process parameters used in the laser internal modification and cutting process are: single pulse energy is 1-5W, pulse width is 10-200ps, scanning speed is 300-1000mm / s, and scanning times are 2-20 times.

2. A composite cutting process for semiconductor materials containing a back gold layer according to claim 1, characterized in that: The depth of the cutting groove is 10-30 μm, the cutting linear speed of the grinding wheel is 30 m / s, and the cutting speed of the grinding wheel is 10 mm / s.

3. The composite cutting process of a semiconductor material containing a back gold layer according to claim 1, characterized in that: Laser scanning forms more than 7 modified layers, all of which are located inside the semiconductor material. The laser power decreases gradually as the laser scans layer by layer.

Citation Information

Patent Citations

  • Wafer processing method

    CN110391183A